(untitled) (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study examined the prevalence and consequences of ethical issues in the administration of teacher education institutions in Delta State. Two purposes and two research questions guided the study. The study adopted a descriptive survey research design. The estimated targeted population for this study consisted of 1, staff strength from two public teacher education institutions in Delta State. The breakdown of this population involves a total of 532 teaching and senior non-teaching staff of Federal College of Education (Technical) Asaba; 510 teaching and senior non-teaching staff of COE, Warri, Delta State. Sample size of the study constituted a total of 521teaching and senior non-teaching staff which included the Deans, Heads of Departments, Directors of units, lecturers and other senior administrative officers across the two public teacher education institutions, selected using the purposive and stratified random sampling techniques. Instrument for data collection was a35-itemclosed-ended structured questionnaire designed by the researcher and titled: “Prevalence and Consequences of Ethical Issues in Administration of Teacher Education Institutions Questionnaire (PCEIATEIQ)”. The questionnaire was structured on a 4-point rating scale of: Strongly Agree (SA) – 4 points, Agree (A)– 3 points, Disagree (D)– 2 points and Strongly Disagree (SD) – 1 point.Both validity and reliability of the questionnaire were established. Data collated were analyzed using mean statistics rated at 2.50 and standard deviation statistics. Findings of the study revealed among others that favouritism, ethnicity, tribalism, bribery, poor accountability, nepotism, mismanagement of funds, political interference, lack of transparency in procurement and resource allocation, sexual harassment, culture of silence around unethical behaviours, academic dishonesty, discriminations, delay in payment of staff honorarium, among others, wereethical issues prevalent in the administration of teacher education institutions in Delta State. From these findings’ recommendations were proffered and among them included that the regulatory agencies for teacher education institutions, that is, the National Universities Commission (NUC) and National Commission for Colleges of Education (NCCE) should establish independent ethics committees to monitor, investigate, and address ethical violations and challenges promptly for effective administration of TEIs in Delta State.